Latin American Identity: Formation, Influences, and Contemporary Studies (Islas, 2025)
Introduction: The study analyzes how Latin American identity originates not only from the memory of the people but also from historical collective consciousness and ways of living and thinking.Methods: Methods such as referential analysis and textual analysis of the content of the reviewed documents were used.Results: Latin American identity is a process built through different horizons of understanding, where diversity is the distinctive feature. Its formation involves various elements such as geopolitics and globalization, which have an impact on current studies on the subject.Conclusions: The visibility of scientific production related to Latin American identity contributes to its better understanding in the global context.
Keywords: geopolitics; globalization; identity; Latin America; cultural studies